Hubungan Pengelolaan Sarana dan Prasarana Berbasis IT Terhadap Peningkatan Produktivitas Kerja Pegawai (Studi Kasus di Kementerian Agama Kabupaten Kulon Progo) - Heru Sulistya; Rinduan Zain (STAI Ma'had Aly Al-Hikam Malang, 2020)
Abstract This research aims to: 1) to know the relationship between facility management and IT-based infrastructures to increase employee work productivity after controlled loyalty; 2) know the relationship between facility management and IT-based infrastructure to employee work productivity. Quantitative research with this correlational study was conducted in the Ministry of Religion of Kulon Progo Regency with a target population of 75 employees. From 75, 66 of which used its data to be further analyzed in this study. Instruments used to collect research data through documentation and questionnaire. Testing the validity of instruments with the formula of Kendallu's tau_b Correlations, while the reliability of instruments was tested with the Cronbach Alpha formula with the significance of the number of correlation coefficient 0.05. While in the Data Analysis section is done by the analysis techniques of bivariate correlation and partial correlation with the help of SPSS (Statistical Product and Social Science) application. The results showed that the management of IT-based facilities and infrastructures (X) was not directly related to increased work productivity (y) because the relationship was mediated by the loyalty of employees (Z). This can be noted from a comparison of bivariate correlation between x and Y variables with the partial correlation between x, y, and z variables. The correlates of Bivariate (ryx) was 0.493 and a partial correlation (ryx. z) of 0.386. Keywords: IT-based facilities and infrastructure, work productivity, loyalty Abstrak Penelitian ini bertujuan untuk: 1) mengetahui hubungan antara pengelolaan sarana dan prasarana berbasis IT terhadap peningkatan produktivitas kerja pegawai setelah dikontrol dengan loyalitas; 2) mengetahui besarnya hubungan antara pengelolaan sarana dan prasarana berbasis IT terhadap produktivitas kerja pegawai. Penelitian kuantitatif dengan studi korelasional ini dilakukan di Kementerian Agama Kabupaten Kulon Progo dengan populasi target sejumlah 75 pegawai. Dari 75, 66 di antaranya digunakan datanya untuk dianalisis lebih lanjut dalam penelitian ini. Instrumen yang digunakan untuk mengumpulkan data penelitian melalui dokumentasi dan kuisioner. Pengujian validitas instrumen dengan rumus Kendalls's tau_b Correlations, sedangkan reliabilitas instrumen diuji dengan rumus Cronbach Alpha dengan signifikansi angka koefisien korelasi 0.05. Sementara pada bagian analisis data dilakukan dengan teknik analisis korelasi bivariat dan korelasi parsial dengan bantuan aplikasi SPSS (Statistical Product and Social Science). Hasil penelitian ini menunjukkan bahawa pengelolaan sarana dan prasarana berbasis IT (x) tidak berhubungan secara langsung terhadap peningkatan produktivitas kerja (y), karena hubungan keduanya dimediasi oleh loyalitas pegawai (z). Hal ini dapat diketahui dari perbandingan korelasi bivariat antara variabel x dan y dengan korelasi parsial antara variabel x, y, dan z. Besaran korelasi bivariat (ryx) adalah 0,493 dan korelasi parsial (ryx.z) 0,386. Kata Kunci: Sarana dan Prasarana Berbasis IT, Produktivitas Kerja, Loyalitas